Peran NU dalam Amar Ma’ruf Nahi Munkar Guna Membina Akhlak Remaja Muslim yang Islami Ditinjau dari Filsafat Etika (Studi Kasus Kecamatan Kotapinang Labuhanbatu Selatan) - Dalimunthe, Isnaini (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2023)
This paper aims to find out: (1) What is the role of MWC NU in broadcasting Amar Ma’ruf Nahi Munkar to Muslim Youth in Kotapinang District (2) What are the factors and obstacles of MWC NU in broadcasting Amar Ma’ruf Nahi Munkar to Muslim Youth in Kotapinang District (3) ) What is the ethics of MWC NU in broadcasting Amar Ma’ruf Nahi Munkar to Muslim Youth in Kotapinang District. The type of research conducted is field research with qualitative methods with a phenomenological approach to religion. This data collection method uses observation, interviews, and documentation. The benefits of this research can provide and increase knowledge about amar Ma’ruf Nahi munkar. The results show that the role of MWC NU in broadcasting amar ma’ruf nahi munkar for youth has gone well with the strategy developed by MWC NU Kotapinang District. Muslim youth and what are the ethics in broadcasting it. In addition, it is necessary for all of us to contribute, not just the government, educational institutions or community organizations to be more active in developing Islamic teachings from all corners of life, especially amar ma’ruf nahi munkar so that Islamic values can characterize Muslim youth so that amar ma’ruf nahi munkar will be carried out not only as a term but will become a habit.Keywords: Nahdlatul Ulama, Amar Ma’ruf Nahi Munkar, Youth.